Hubungan Antara Dukungan Sosial Dengan Penyesuaian Diri Remaja Di Panti Asuhan - Kumalasari, Fani; Ahyani, Latifah Nur (Jurnal Psikologi: PITUTUR, 2012)
The purpose of this study is to investigate empirically the relationshipbetween social support with adjustment in adolescents in an orphanage. The subjects of this study are adolescents between the ages of 13 to 18 years in the Orphanage Darul Hadlonah Kudus. Method sampling using Quota Non Random Sampling.Measuring tool used is the scale of social support have been prepared on aspects raised by Sarafino in Oktavia, L (2002, p.17-18) which includesemotional  support,  support  award,  instrumental  support,  and support information. While the adjustment scale of self-prepared on aspects raised by Pramadi (1996, h.240) which covers aspects of Self Knowledge and Self Insight,  aspect  Objectifity Self  Acceptance  and  Self,  the  aspect  of  Self Development and Self Control, Satisfaction aspect.Based on the analysis of research data with Product Moment by SPSS15.0  for  Windows  obtained  from  both  the  correlation  coefficient  rxy amounted to 0.339 with p of 0.011 (p <0.05) this means the hypothesis is accepted  and  showed  relationship  between  social  support  with  adolescent adjustment in an orphanage.